The relationships between motor practice, temperament and motor skills in term and preterm infants - Jensen, Lynn Marise (Curtin University, 2015)
This study examined gross and fine motor skills, temperament profiles and the duration and intensity of motor practice in 93 term and 87 preterm infants at corrected age. Overall, more intense practice was associated with better gross motor skills and a high extraversion temperament predicted more intense practice. Importantly, infants who were small for gestational age practiced less intensely and had a higher risk of fine motor delay, as did male infants.